"Manipulation" of Crystal Structure by Methylthiolation Enabling Ultrahigh Mobility in a Pyrene‐Based Molecular Semiconductor (Adv. Mater. 32/2021). Issue 32 (12th August 2021) - Takimiya, Kazuo; Bulgarevich, Kirill; Abbas, Mamatimin; Horiuchi, Shingo; Ogaki, Takuya; Kawabata, Kohsuke; Ablat, Abduleziz
Abstract : Packing Structures The sandwich herringbone structure of pyrene is effectively "manipulated" by four‐fold methylthiolation by Kazuo Takimiya and co‐workers in article number 2102914 to realize a new‐type of a brickwork packing structure, which turns out to be an ideal channel material for single‐crystal organic‐field‐effect transistors, showing mobility higher than 30 cm 2 V −1 s −1 and band‐like transport down to 230 K.